2003
DOI: 10.1186/1472-6963-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting general practitioners' decisions about plain radiography for back pain: implications for classification of guideline barriers – a qualitative study

Abstract: Background: General practitioners often diverge from clinical guidelines regarding spine radiography. This study aimed to identify and describe A) factors general practitioners consider may affect their decisions about ordering plain radiography for back pain and B) barriers to guideline adherence suggested by such factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 33 publications
5
121
2
3
Order By: Relevance
“…This study also found that, given the choice, over 80% of patients would have an x-ray. A review of three qualitative studies involving primary care doctors found that patient preference influenced their decision to order spinal radiography [5]. Patient requests for tests that are not indicated medically can be counteracted by providing information to explain this.…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also found that, given the choice, over 80% of patients would have an x-ray. A review of three qualitative studies involving primary care doctors found that patient preference influenced their decision to order spinal radiography [5]. Patient requests for tests that are not indicated medically can be counteracted by providing information to explain this.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…Patient preference, either to undergo or not undergo testing or for one test over another, can influence test ordering [3,5,13,17,20,30]. The acceptability of the test to the patient, for example in terms of invasiveness or side effects, and the impact of the potential diagnosis on the patient may affect a doctor's decision to order a test [30].…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that diagnostic procedures differ amongst different cultural settings [21,84]. For example, radiographic procedures for LBP patients and clinical decision making among professionals differ across countries [2,31]. Cross-country differences have also been found to exist in medical, physical and psychosocial findings as well as in the management across LBP sufferers of different cultural backgrounds [15,82,86,98].…”
Section: Introductionmentioning
confidence: 99%
“…They may order imaging for low back pain to appear to be "doing something," or from fear of litigation. [16][17][18][19][20][21] Health system-level factors that may influence these physician behaviors include local practice customs; incentives to follow guidelines (or, conversely, to provide care that patients request); time restraints; and access to automated reminders in the EHR, counseling materials, and radiology services. [19][20][21] The purpose of these analyses was to generate hypotheses for further exploration and development of interventions.…”
Section: Introductionmentioning
confidence: 99%